A medium frequency induction furnace ramming material and preparation method thereof

By pretreating the magnesium-aluminum spinel in the rammed material of the medium frequency induction furnace and mixing it with nanotitanium dioxide and nanozinc oxide, the problem of the material being prone to cracking or peeling at high temperatures is solved, and the high-temperature flexural performance and service life of the material are improved.

CN117164369BActive Publication Date: 2025-03-21LENGSHUIJIANG BOSHENG NEW MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311137227.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-05
Publication Date
2025-03-21
Estimated Expiration
2043-09-05

AI Technical Summary

Technical Problem

In the ramming material of the medium frequency induction furnace, single addition of corundum material is prone to cracking, while simple addition of magnesium material is prone to permeation by the slag, resulting in the problem of material peeling.

Method used

Pretreatment by magnesium aluminum spinel, a strong acid solution is used to replace some of the magnesium ions, and the interlayers are dehydrated through the calcination process to form a mesoporous structure. The pretreated magnesium-aluminum spinel is then mixed with nanotitanium dioxide and aqueous binder solution, and then evenly ground to form a blank, and finally sintered at high temperature.

Benefits of technology

By introducing nanotitanium dioxide and nano zinc oxide, uniformly dissolve into the spinel crystal structure, reducing the stress unevenness of the material, avoiding the cracking or peeling of the material, and improving the service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004432235150000061
    Figure BDA0004432235150000061
  • Figure BDA0004432235150000071
    Figure BDA0004432235150000071
Patent Text Reader

Abstract

This invention belongs to the field of refractory materials technology, specifically relating to a ramming material for a medium-frequency induction furnace and its preparation method. The preparation process includes: pretreatment of magnesium aluminum spinel: mixing and reacting magnesium aluminum spinel with a strong acid solution, filtering, washing and drying to obtain acid-impregnated magnesium aluminum spinel; calcining the obtained acid-impregnated magnesium aluminum spinel at a temperature of 180-200℃ for 3-5 hours, cooling and discharging to obtain pretreated magnesium aluminum spinel; raw material mixing: taking 100-120 parts by weight of pretreated magnesium aluminum spinel, 4-6 parts by weight of nano titanium dioxide, and 10-15 parts by weight of aqueous binder solution, ball milling and mixing evenly, and pressing into a green blank; sintering: drying the green blank, heat-treating it at a temperature of 1500-1600℃ for 3-5 hours, cooling and discharging to obtain the product; the magnesium aluminum spinel used in the pretreatment process has a particle size distribution range of 10-15μm; and the D50 of the nano titanium dioxide is 10-30nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of refractory materials, and more specifically, relates to a medium frequency induction furnace ramming material and a preparation method thereof. Background Art

[0002] Medium frequency induction furnaces are widely used in casting, steelmaking and nonferrous smelting due to their flexibility, energy saving, high efficiency, low pollution and easy adjustment of composition. The lining material is one of the most important components of the induction furnace. Its quality is not only related to the quality of the smelting technology, but also affects the cost, efficiency and safety of production.

[0003] The current smelting environment is generally alkaline, and the use of acid ramming materials will affect the life of the induction furnace lining. Corundum has good thermal stability, small thermal expansion coefficient, and excellent corrosion resistance, but corundum dry ramming materials still have disadvantages such as low smelting furnace, difficult to control sintering and expansion, which will lead to problems such as cracking of the lining. Adding a certain amount of magnesia can inhibit the cracking of the corundum lining.

[0004] Magnesium materials have good resistance to slag erosion, but are easily penetrated by molten slag, resulting in peeling. Therefore, how to effectively prevent the furnace lining material from being penetrated by molten slag after adding magnesium materials and extend the service life of the product is one of the difficult problems faced by technical personnel in this field. Summary of the invention

[0005] The technical problem to be solved by the present invention is that for commonly used medium frequency induction furnace ramming materials, a single addition of corundum material is prone to cracking, while a simple addition of magnesium material is easily infiltrated by slag, resulting in material peeling. A medium frequency induction furnace ramming material and a preparation method thereof are provided.

[0006] The purpose of the invention is to provide a method for preparing a medium frequency induction furnace ramming mass.

[0007] Another object of the present invention is to provide a medium frequency induction furnace ramming material.

[0008] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0009] A method for preparing a medium frequency induction furnace ramming material, the specific preparation steps comprising:

[0010] Magnesium aluminum spinel pretreatment:

[0011] The magnesium aluminum spinel and the strong acid solution are mixed and reacted, filtered, washed and dried to obtain the acid-leached magnesium aluminum spinel;

[0012] Firstly, the magnesium-aluminum spinel is treated with a strong acid solution, during which hydrogen ions ionized by the strong acid solution replace part of the magnesium ions between the magnesium-aluminum spinel layers;

[0013] The obtained acid-leached magnesium-aluminum spinel is calcined at a temperature of 180-200° C. for 3-5 hours, cooled, and discharged to obtain pretreated magnesium-aluminum spinel;

[0014] The magnesia-alumina spinel treated with strong acid is calcined at a set temperature to dehydrate the interlayer hydroxyl groups. During the dehydration process, the diffusion of water molecules causes the internal micropores to be transformed into mesopores, which facilitates the mass transfer process during the subsequent high-temperature sintering process.

[0015] Raw material mixing:

[0016] According to weight, 100-120 parts of pretreated magnesium aluminum spinel, 4-6 parts of nano titanium dioxide, and 10-15 parts of aqueous binder solution are taken, ball-milled and mixed evenly, and then pressed into a green blank;

[0017] sintering:

[0018] After the green body is dried, it is heat treated at a temperature of 1500-1600°C for 3-5 hours, cooled, and discharged to obtain the product.

[0019] The above scheme introduces nano titanium dioxide. First, nano-sized titanium dioxide can diffuse and penetrate smoothly in the above-mentioned calcined magnesium-aluminum spinel result. Secondly, in the mesoporous structure of magnesium-aluminum spinel, titanium element is more easily and evenly dissolved into the spinel crystal structure, so that different parts of the spinel undergo more uniform lattice distortion, so that the crystal defect concentration in different parts of the crystal remains relatively consistent as much as possible, and the activation energy required for sintering different parts of the material is reduced while ensuring that the reduction range remains as consistent as possible; in this way, the stress in different parts can be kept uniform, avoiding the occurrence of local stress unevenness that causes material cracking or peeling. In addition, after some magnesium ions are replaced, it is easier to expose the aluminum oxide in the spinel structure, making it easier to react with titanium dioxide to form Al2TiO5, thereby preventing the generation and expansion of surface cracks and increasing the service life of the product.

[0020] Furthermore, the strong acid solution is selected from any one of hydrochloric acid, nitric acid or sulfuric acid; the mass fraction of the strong acid solution is 5-8%.

[0021] Furthermore, the aqueous adhesive solution is selected from any one of a dextrin solution, a carboxymethyl cellulose solution, and a polyvinyl alcohol solution; and the mass fraction of the aqueous adhesive solution is 10-15%.

[0022] Furthermore, during the pretreatment of the magnesium-aluminum spinel, the particle size distribution range of the magnesium-aluminum spinel used is 10-15 μm; and the D50 of the nano titanium dioxide is 10-30 nm.

[0023] By selecting magnesium aluminate spinel of a suitable size range and a suitable particle size distribution range, the gaps formed by the accumulation of particles during the process of making the blank are relatively uniform. This makes it easier for smaller nano-titanium dioxide to be evenly distributed in the gaps, avoiding excessive filling of local nano-titanium dioxide, which would affect the reaction uniformity during the subsequent sintering process.

[0024] Furthermore, the ball milling and mixing uniformly includes: adding zirconium oxide ball milling beads according to a ball-to-material mass ratio of 20:1-25:1, and ball milling and mixing for 3-5 hours at a revolution speed of 400-600 r / min and a rotation speed of 300-500 r / min.

[0025] Furthermore, the raw material mixing process also includes adding 1.0-1.5% of the mass of the pretreated magnesium aluminum spinel nano zinc oxide.

[0026] Furthermore, the D50 of the nano zinc oxide is 3-8nm.

[0027] By further introducing nano zinc oxide and selecting a suitable size range, it is smaller than nano titanium dioxide. In this way, it can act as a lubricant to assist the uniform dispersion of nano titanium dioxide during the ball milling process, and after being coated on the surface of nano titanium dioxide, it can work together with it as a flux, which is conducive to the formation of continuous and stable products during the sintering process.

[0028] A medium frequency induction furnace ramming material is prepared by adopting the above preparation method. DETAILED DESCRIPTION

[0029] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0030] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0031] A method for preparing a medium frequency induction furnace ramming material, the specific preparation steps comprising:

[0032] Pretreatment of magnesium-aluminum spinel: After the magnesium-aluminum spinel and the strong acid solution are mixed and reacted, the mixture is filtered, washed and dried to obtain acid-leached magnesium-aluminum spinel; the obtained acid-leached magnesium-aluminum spinel is roasted at a temperature of 180-200° C. for 3-5 hours, cooled and discharged to obtain pretreated magnesium-aluminum spinel;

[0033] Raw material mixing: by weight, take 100-120 parts of pretreated magnesium aluminum spinel, 4-6 parts of nano titanium dioxide, and 10-15 parts of aqueous binder solution, mix them evenly with ball mill, and press them into green blanks;

[0034] Sintering: After the green body is dried, heat-treated at 1500-1600℃ for 3-5h, cooled and discharged to obtain the product.

[0035] Example 1

[0036] Magnesium aluminum spinel pretreatment:

[0037] A magnesium-aluminum spinel with a particle size distribution range of 10-15 μm and a strong acid solution with a mass fraction of 5% are mixed in a mass ratio of 1:5 and poured into a reactor. The mixture is stirred at a temperature of 45° C. and a stirring speed of 600 r / min for 2 hours at a constant temperature. The mixture is filtered, the filter cake is collected, and the filter cake is washed with deionized water until the washing liquid is neutral. The washed filter cake is then transferred to an oven and dried to a constant weight at a temperature of 80° C. to obtain acid-leached magnesium-aluminum spinel.

[0038] Wherein, the strong acid solution is selected from hydrochloric acid;

[0039] The obtained acid-leached magnesium-aluminum spinel was transferred to a tube furnace, heated to 180°C at a rate of 3°C / min, kept warm and roasted for 3 hours, cooled to room temperature with the furnace, and discharged to obtain pretreated magnesium-aluminum spinel;

[0040] Raw material mixing:

[0041] According to the weight percentage, 100 parts of pretreated magnesium aluminum spinel, 4 parts of nano titanium dioxide, and 10 parts of aqueous binder solution are taken, mixed and poured into a ball mill, and 1.0% of the weight of the pretreated magnesium aluminum spinel is added with nano zinc oxide, and zirconium oxide ball milling beads are added according to the ball-to-material mass ratio of 20:1, and the ball milling is mixed for 3 hours at a revolution speed of 400 r / min and a rotation speed of 300 r / min to obtain a ball mill material;

[0042] The obtained ball mill material is cold pressed under a pressure of 50 MPa to obtain a green blank;

[0043] Wherein, the aqueous adhesive solution is selected from a dextrin solution; the mass fraction of the aqueous adhesive solution is 10%;

[0044] The D50 of the nano titanium dioxide is 10nm; the D50 of the nano zinc oxide is 3nm;

[0045] sintering:

[0046] The green billet was transferred into an oven, dried to constant weight at 100°C, transferred into a sintering furnace, heated to 1500°C at a rate of 6°C / min, sintered for 3 hours, cooled to room temperature with the furnace, and discharged to obtain the product.

[0047] Example 2

[0048] Magnesium aluminum spinel pretreatment:

[0049] A magnesium-aluminum spinel with a particle size distribution range of 10-15 μm and a strong acid solution with a mass fraction of 5-8% are mixed in a mass ratio of 1:8 and poured into a reactor. The mixture is stirred at a temperature of 50° C. and a stirring speed of 700 r / min for 3 hours at a constant temperature. The mixture is filtered, the filter cake is collected, and the filter cake is washed with deionized water until the washing liquid is neutral. The washed filter cake is then transferred to an oven and dried to a constant weight at a temperature of 85° C. to obtain acid-leached magnesium-aluminum spinel.

[0050] Wherein, the strong acid solution is selected from nitric acid;

[0051] The obtained acid-leached magnesium-aluminum spinel was transferred to a tube furnace, heated to 190°C at a rate of 4°C / min, kept warm and roasted for 4 hours, cooled to room temperature with the furnace, and discharged to obtain pretreated magnesium-aluminum spinel;

[0052] Raw material mixing:

[0053] According to the weight percentage, 110 parts of pretreated magnesium aluminum spinel, 5 parts of nano titanium dioxide, and 12 parts of aqueous binder solution are mixed and poured into a ball mill, and 1.2% of the weight of the pretreated magnesium aluminum spinel is added with nano zinc oxide, and zirconium oxide ball milling beads are added according to the ball-to-material mass ratio of 22:1, and the ball milling is mixed for 4 hours at a revolution speed of 500r / min and a rotation speed of 400r / min to obtain a ball mill material;

[0054] The obtained ball mill material is cold pressed under a pressure of 55 MPa to obtain a green blank;

[0055] Wherein, the aqueous binder solution is selected from carboxymethyl cellulose solution; the mass fraction of the aqueous binder solution is 12%;

[0056] The D50 of the nano titanium dioxide is 20nm; the D50 of the nano zinc oxide is 5nm;

[0057] sintering:

[0058] The green billet is transferred into an oven, dried to constant weight at 105°C, transferred into a sintering furnace, heated to 1550°C at a rate of 7°C / min, sintered for 4 hours, cooled to room temperature with the furnace, and discharged to obtain the product.

[0059] Example 3

[0060] Magnesium aluminum spinel pretreatment:

[0061] A magnesium-aluminum spinel with a particle size distribution range of 10-15 μm and a strong acid solution with a mass fraction of 8% are mixed in a mass ratio of 1:10 and poured into a reactor. The mixture is stirred at a temperature of 55° C. and a stirring speed of 800 r / min for 4 hours at a constant temperature. The mixture is filtered, the filter cake is collected, and the filter cake is washed with deionized water until the washing liquid is neutral. The washed filter cake is then transferred to an oven and dried to a constant weight at a temperature of 90° C. to obtain acid-leached magnesium-aluminum spinel.

[0062] Wherein, the strong acid solution is selected from sulfuric acid;

[0063] The obtained acid-leached magnesium-aluminum spinel was transferred to a tube furnace, heated to 200°C at a rate of 5°C / min, kept warm and roasted for 5 hours, cooled to room temperature with the furnace, and discharged to obtain pretreated magnesium-aluminum spinel;

[0064] Raw material mixing:

[0065] 120 parts of pretreated magnesium aluminum spinel, 6 parts of nano titanium dioxide, and 15 parts of aqueous binder solution are mixed and poured into a ball mill, and 1.5% of the mass of the pretreated magnesium aluminum spinel is added with nano zinc oxide, and zirconium oxide ball milling beads are added according to the ball-to-material mass ratio of 25:1, and the mixture is ball milled and mixed for 5 hours at a revolution speed of 600 r / min and a rotation speed of 500 r / min to obtain a ball mill material;

[0066] The obtained ball mill material is cold pressed under a pressure of 60 MPa to obtain a green blank;

[0067] Wherein, the aqueous adhesive solution is selected from polyvinyl alcohol solution; the mass fraction of the aqueous adhesive solution is 15%;

[0068] The D50 of the nano titanium dioxide is 30nm; the D50 of the nano zinc oxide is 8nm;

[0069] sintering:

[0070] The green billet is transferred into an oven, dried to constant weight at 110°C, transferred into a sintering furnace, heated to 1600°C at a rate of 8°C / min, sintered for 5 hours, cooled to room temperature with the furnace, and discharged to obtain the product.

[0071] Example 4

[0072] The difference between this embodiment and embodiment 1 is that nano zinc oxide is not added, and other conditions remain unchanged.

[0073] Example 5

[0074] The present embodiment is different from the embodiment 1 in that the nano zinc oxide with a D50 of 10 nm is used to replace the nano zinc oxide with a D50 of 3 nm, and the other conditions remain unchanged.

[0075] Example 6

[0076] The present embodiment is different from the embodiment 1 in that the particle size distribution range of the magnesium-aluminum spinel is selected to be 1-100 μm, and the other conditions remain unchanged.

[0077] Comparative Example 1

[0078] The difference between this comparative example and Example 1 is that titanium dioxide particles with a D50 of 10 μm of equal mass are used to replace nano titanium dioxide with a D50 of 10 nm, and other conditions remain unchanged.

[0079] Comparative Example 2

[0080] The difference between this comparative example and Example 1 is that the acid-leached magnesium aluminum spinel is not calcined, and the other conditions remain unchanged.

[0081] Comparative Example 3

[0082] The difference between this comparative example and Example 1 is that an acetic acid solution of equal mass is used to replace the hydrochloric acid solution, and other conditions remain unchanged.

[0083] The performance tests were performed on the products obtained in Examples 1-6 and Comparative Examples 1-3. The specific test methods and test results are as follows:

[0084] Take circular specimens with the same specifications of 20mm diameter and 18mm thickness, test the radial linear change rate of the specimens according to GB / T5988-2007, and use the three-point bending method to test the high-temperature flexural strength of the specimens at 1400℃ after 30min of heat preservation according to GB / T 3002-2004. The specific test results are shown in Table 1.

[0085] Table 1: Product performance test results

[0086]

[0087]

[0088] It can be seen from the test results in Table 1 that the product obtained by the technical solution of the present invention has a low radial line change rate and excellent high-temperature bending resistance. It can maintain the structure more stably, avoid peeling and cracking, and extend the service life of the product.

[0089] Blank example:

[0090] Raw material mixing:

[0091] According to weight, 100 parts of artificial corundum, 10 parts of magnesia, 4 parts of nano titanium dioxide, and 10 parts of aqueous binder solution are mixed and poured into a ball mill, and 1.0% of the weight of the artificial corundum is added with nano zinc oxide, and zirconium oxide ball milling beads are added according to the ball-to-material mass ratio of 20:1, and the ball milling is performed for 3 hours at a revolution speed of 400 r / min and a rotation speed of 300 r / min to obtain a ball mill;

[0092] The obtained ball mill material is cold pressed under a pressure of 50 MPa to obtain a green blank;

[0093] Wherein, the aqueous adhesive solution is selected from a dextrin solution; the mass fraction of the aqueous adhesive solution is 10%;

[0094] The D50 of the nano titanium dioxide is 10nm; the D50 of the nano zinc oxide is 3nm;

[0095] sintering:

[0096] The green billet was transferred into an oven, dried to constant weight at 100°C, transferred into a sintering furnace, heated to 1500°C at a rate of 6°C / min, sintered for 3 hours, cooled to room temperature with the furnace, and discharged to obtain the product.

[0097] The performance test of the product obtained from the blank example was carried out. Specifically, a circular sample with the same specifications of 20 mm in diameter and 18 mm in thickness was taken, and the radial linear change rate of the sample was tested according to GB / T 5988-2007. The test result was 5.09%. The high-temperature flexural strength of the sample after being kept warm for 30 minutes at 1400°C was determined by the three-point bending method according to GB / T3002-2004, and the test result was 1.69 MPa.

[0098] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a medium frequency induction furnace ramming mass, characterized in that: The specific preparation steps include: Magnesium aluminum spinel pretreatment: The magnesium aluminum spinel and the strong acid solution are mixed and reacted, filtered, washed and dried to obtain the acid-leached magnesium aluminum spinel; The particle size distribution range of the magnesium aluminum spinel is 10-15 μm; The obtained acid-leached magnesium-aluminum spinel is calcined at a temperature of 180-200° C. for 3-5 hours, cooled, and discharged to obtain pretreated magnesium-aluminum spinel; Raw material mixing: According to weight, 100-120 parts of pretreated magnesium aluminum spinel, 4-6 parts of nano titanium dioxide, and 10-15 parts of aqueous binder solution are taken, ball-milled and mixed evenly, and then pressed into a green blank; The D50 of the nano titanium dioxide is 10-30nm; sintering: After the green body is dried, it is heat treated at a temperature of 1500-1600°C for 3-5 hours, cooled, and discharged to obtain the product.

2. The method for preparing a medium frequency induction furnace ramming mass according to claim 1, characterized in that: The strong acid solution is selected from any one of hydrochloric acid, nitric acid or sulfuric acid; the mass fraction of the strong acid solution is 5-8%.

3. The method for preparing a medium frequency induction furnace ramming material according to claim 1, characterized in that: The aqueous adhesive solution is selected from any one of a dextrin solution, a carboxymethyl cellulose solution and a polyvinyl alcohol solution; the mass fraction of the aqueous adhesive solution is 10-15%.

4. The method for preparing a medium frequency induction furnace ramming mass according to claim 1, characterized in that: The ball milling and mixing uniformly comprises: adding zirconium oxide ball milling beads according to a ball-to-material mass ratio of 20:1-25:1, and ball milling and mixing for 3-5 hours at a revolution speed of 400-600 r / min and a rotation speed of 300-500 r / min.

5. The method for preparing a medium frequency induction furnace ramming mass according to claim 1, characterized in that: The raw material mixing process also includes adding nano zinc oxide in an amount of 1.0-1.5% by mass of the pretreated magnesium aluminum spinel.

6. The method for preparing a medium frequency induction furnace ramming mass according to claim 5, characterized in that: The D50 of the nano zinc oxide is 3-8nm.

7. A medium frequency induction furnace ramming material, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Permeable dry stamp mass for furnace bottom of intermediate frequency furnace

    CN102775159A

  • New method for synthesizing high specific surface ??magnesium-aluminum spinel

    CN102838145A

  • Magnesium aluminate spinel brick with excellent comprehensive performance and moderate price and preparation method thereof

    CN113213956A

  • Low-carbon magnesia spinel sliding plate brick and preparation method thereof

    CN114057472A